United Republic of Tanzania : First Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
The Tanzanian economy performed better than expected in the face of adverse shocks owing to supportive fiscal and monetary policies. The government is committed to contain and prioritize public spending. Further strengthening of investment and debt management processes is an urgent priority. Structural reforms will continue to support financial deepening and enhanced public financial management. Over the medium term, maintaining social gains and the growth momentum will require more widening fiscal changes with the objectives of both stepping up domestic revenue mobilization and increasing spending efficiency.